Milet, Türkei: Denkmalpflege - Niewöhner, Philipp (e-Forschungsberichte des DAI, 2023)
Miletus is a large multi-period site and requires various conservation, restoration and site management projects. In 2012 to 2014 these included the Roman Baths of Faustina, the late Byzantine chapel of Hagia Paraskevi, the ancient theatre and a Byzantine castle on top of it, as well as the ancient street grid and its use by modern visitors. The projects continue a long tradition that goes back to the early 20th century, when Miletus started to be excavated and conserved. Over time, continuous conservation and site management work at Miletus has established local conventions that are easily recognizable, self-explanatory and help the visitor understand a complex settlement including many architectural styles and a wide range of cultures.